DNA lipid nanoparticle vaccine targeting outer surface protein C affords protection against homologous Borrelia burgdorferi needle challenge in mice - Pfeifle, Annabelle; Thulasi Raman, Sathya N.; Lansdell, Casey; Zhang, Wanyue; Tamming, Levi; Cecillon, Jonathon; Laryea, Emmanuel; Patel, Devina; Wu, Jianguo; Gravel, Caroline; Frahm, Grant; Gao, Jun; et al. (Frontiers in Immunology, 2023)
Introduction The incidence of Lyme disease (LD) in Canada and the United States has risen over the last decade, nearing 480,000 cases each year. Borrelia burgdorferi sensu lato, the causative agent of LD, is transmitted to humans through the bite of an infected tick, resulting in flu-like symptoms and often a characteristic bull’s-eye rash. In more severe cases, disseminated bacterial infection can cause arthritis, carditis and neurological impairments. Currently, no vaccine is available for the prevention of LD in humans. Methods In this study, we developed a lipid nanoparticle (LNP)-encapsulated DNA vaccine encoding outer surface protein C type A (OspC-type A) of B. burgdorferi. Results Vaccination of C3H/HeN mice with two doses of the candidate vaccine induced significant OspC-type A-specific antibody titres and borreliacidal activity. Analysis of the bacterial burden following needle challenge with B. burgdorferi (OspC-type A) revealed that the candidate vaccine afforded effective protection against homologous infection across a range of susceptible tissues. Notably, vaccinated mice were protected against carditis and lymphadenopathy associated with Lyme borreliosis. Discussion Overall, the results of this study provide support for the use of a DNA-LNP platform for the development of LD vaccines.